The Impact of Demand on Cargo Dwell Time in Ports in SSA - Beuran, Monica (World Bank, Washington, DC, 2014)
Long cargo dwell times in ports are a critical issue in Sub-Saharan African countries since they result in slow import processes and are bound to dramatically reduce trade. The main objective of this study is to analyze long dwell times' causes in ports in Sub-Saharan Africa from a shipper's perspective. The findings point to the crucial importance of private sector practices and incentives. The authors argue in the case of Sub-Saharan African countries that private operators, rather than being advocates of reforms in this area, might be responsible for the failures of many of these initiatives. It seems that in Sub-Saharan Africa importers' and freight forwarders' professionalism, cash constraints and operators' strategies are some of the factors that have a major impact on cargo dwell time. Low competency, cash constraints and low storage tariffs explain why most importers have little incentive to reduce cargo dwell time since in most cases, this would increase their input costs. However, monopolists/cartels may have a stronger incentive to reduce cargo dwell time but only in order to maximize their profit (and would not adjust prices downward).